Внутрішньокорпоративні фінансові потоки у системі управління підприємством - Шкварчук, Л. О.; Слав’юк, Р. А.; Shkvarchuk, L.; ASlav`yuk, R. (Видавництво Львівської політехніки, 2019)
У статті проведено дослідження форм та структури фінансових потоків, які виникають між різними учасниками інтегрованих структур як у вертикальній, так й горизонтальній площині. Авторами здійснено оцінювання обсягів внутрішньокорпоративних фінансових потоків найбільших холдингових структур в Україні. Загальна сума згенерованого фінансового потоку у межах інтегрованої структури є значною і у деяких випадках сягає величини більше ніж 80 % від загальної суми активів материнської компанії. Загалом структура внутрішньокорпоративних фінансових потоків є ідентичною для більшості суб’єктів і не залежить від виду діяльності, організаційної будови та форми власності. Найбільшим елементом таких потоків є поворотна фінансова допомога, яка пов’язує найчастіше материнську та дочірні компанії. У сучасних умовах формування відповідних потоків часто здійснюється з метою маніпулювання показниками фінансового стану підприємств, причому і у бік завищення, і заниження. Згідно з проведеним аналізом обґрунтовано необхідність врахування елементів внутрішньокорпоративних фінансових потоків при здійсненні незалежного оцінювання фінансового стану як дочірніх підприємств, так й материнської компанії. Автори визначили перелік відповідних показників у фінансовій звітності корпорації, а також запропонували інтерпретацію відповідних характеристик.

This study reviews the relationships between the company’s financial flows managing and the results. The purpose of this paper is to evaluate the peculiarities of the financial flows of corporation by dividing their main elements and investigating them separately. We present the research on holding companies. Recently, debate on corporate financial flows’ has received greater attention in the corporate finance literature. Corporate finance theories provide competing hypotheses on the relationship between cash holdings and corporate performance. But according our study there are no direct correlation between corporate financial flows’ and corporate performance in Ukraine. The reasons of such confusion include differences in the purpose of forming intracorporate financial flows. Sometimes corporate pursue the goal of financial wealth only through financial coordination between the parent corporations and the subsidiaries. It’s typically for corporates in Ukraine to accumulate the great input cash flows from the parent corporations to the subsidiaries. Ukrainian holdings tend to accumulate intracorporate financial flows with the intent of creating a financial safety net for themselves in anticipation of future economic downturns. We found that 80% of the holding assets are formed as a contribution to the authorized capital of the subsidiaries. The structure of intra-corporate financial flows is identical for most entities and does not depend on the type of activity, organizational structure and ownership. The main element of such flows is the financial assistance, which most often connects the parent company and subsidiary. We argue that it’s necessary to allow the elements of intra-corporate financial flows for the independent assessment of the financial position of both subsidiaries and parent companies. We also have identified a list of relevant indicators in the financial statements of the corporation needed for this purpose.
Intra-corporate financial flows in the corporate management system
Keywords: інтегрована структура; фінансовий потік; фінансова допомога; інвестиції у дочірні підприємства; holding company; financial flow; financial assistance; investments in subsidiaries; 658.14.17